Impact of Transport Infrastructure on Living Standards: Evidence from the Chinese Provinces Directly Affected by the "One Belt, One Road" Initiative - Rim, Gwang-Nam; An, Chol-Ju (Business Perspective Review, 2022)
Purpose: This paper discusses the impact of transport infrastructure on living standards in the Chinese provinces directly affected by the “One Belt, One Road” initiative. Methods: The impact of transport infrastructures such as railways and highways on people’s living standards, more specifically, the household consumption level in the Chinese provinces directly affected by the "One Belt, One Road" was analyzed based on data from 2008 to 2017 from National Bureau of Statistics of China and some databases related to the "One Belt, One Road". Descriptive statistics, correlation, and regression were applied for analysis. Results: a)The living standards are not improved in proportion to the development level of railways and highways due to influences of various factors on living standards, b) the development level of transport infrastructure does not have enough impact on reducing the gap in living standards between urban and rural areas in the Chinese provinces under study, c) the development level of transport infrastructure has a relatively more significant impact on living standards in coastal provinces than inland provinces under study, and d) in the future, the measures to develop the transport infrastructure may provably contribute to achieving targets for enhancing the living standards under the realization of the “One Belt, One Road” initiative. Implications: To enhance the living standard, the management of investment in transport infrastructure as well as other factors, such as employment, income distribution, supply of goods and services, price level, etc. affecting people’s living standard ought to be improved in line with the features of a given region.